Applying social network analysis to identify project critical success factors - Nunes, Marco (2021)
A key challenge in project management is to understand to which extent the dynamic interactions between the different project people-through formal and informal networks of collaboration that temporarily emerge across a project's lifecycle-throughout all the phases of a project lifecycle, influence a project's outcome. This challenge has been a growing concern to organizations that deliver projects, due their huge impact in economic, environmental, and social sustainability. In this work, a heuristic two-part model, supported with three scientific fields-project management, risk management, and social network analysis-is proposed, to uncover and measure the extent to which the dynamic interactions of project people-as they work through networks of collaboration-across all the phases of a project lifecycle, influence a project's outcome, by first identifying critical success factors regarding five general project collaboration types (1) communication and insight, (2) internal and cross collaboration, (3) know-how and power sharing, (4) clustering, and (5) teamwork efficiency) by analyzing delivered projects, and second, using those identified critical success factors to provide guidance in upcoming projects regarding the five project collaboration types.